Developing a postgraduate professional education framework for emergency nursing: a co-design approach - Karen A. Theobald; Fiona Maree Coyer; Amanda Jane Henderson; Robyn Fox; Bernadette F. Thomson; Alexandra L. McCarthy (BMC, 2021)
Abstract Background Hospital and university service providers invest significant but separate resources into preparing registered nurses to work in the emergency department setting. This results in the duplication of both curricula and resource investment in the health and higher education sectors. This paper describes an evidence-based co-designed study with clinical-academic stakeholders from hospital and university settings. Methods The study was informed by evidence-based co-design, using emergency nursing as an exemplar. Eighteen hours of co-design workshops were completed with 21 key clinical-academic stakeholders from hospital and university settings. Results Outcomes were matrices synchronising professional and regulatory imperatives of postgraduate nursing coursework; mutually-shaped curriculum content, teaching approaches and assessment strategies relevant for postgraduate education; a new University-Industry Academic Integration Framework; five agreed guiding principles of postgraduate curriculum development for university-industry curriculum co-design; and a Graduate Certificate of Emergency Nursing curriculum exemplar. Conclusion Industry-academic service provider co-design can increase the relevance of postgraduate specialist courses in nursing, strengthening the nexus between both entities to advance learning and employability. The study developed strategies and exemplars for future use in any mutually determined academic-industry education partnership.